Effectiviness Of Roleplaying Technique In Reduce Verbal Bullying Behavior In Junior High School Students - Agustin, Amilia Fika; Rahmawati, Weni Kurnia; Fauziyah, Nailul (Jurnal Kiprah Pendidikan, 2025)
This research aims to examine the effectiveness of roleplaying technique in reducing verbal bullying behavior. Verbal bullying is a form of Numbern physical violence that frequently occurs among students and has negative impacts on the emotional and social development of victims. This behavior includes mocking, insulting, threatening, and using demeaning language. The roleplaying technique was chosen as a guiandce approach that allows students to play roles in specific social situations. Through this simulation, students are expected to understand others' perspectives, develop empathy, and improve their communication methods. This research is a quantitative study using a quasi-experimental design, specifically a One Group Pretest-Posttest Design. Subjects were given a pre-test, then received treatment in the form of group guiandce services through roleplaying technique, and subsequently given a post-test. The research instrument used a validated verbal bullying behavior scale with data Numberrmality testing using the Shapiro-Wilk test and homogeneity test. The roleplaying intervention was conducted over 4 sessions with a duration of 90 minutes per session. Data analysis technique used paired t-test with a significance level of 0.05. Based on the research results, it can be concluded that there was a significant decrease in verbal bullying behavior from an average score of 173.875 (pretest) to 102.625 (posttest) with a p-value = 0.000 (p < 0.05). Based on the research findings, the roleplaying technique proved effective in reducing verbal bullying behavior among junior high school students. This research contributes to the development of anti-bullying intervention strategies in school environments and can serve as an alternative method that can be implemented to address similar problems in other educational institutions.